Analisis dan Pemodelan Proses Bisnis Katering pada UMKM Menggunakan BPMN - Hananto, April Lia; Rosalina, Elsa; Hananto, Agustia; Huda, Baenil (INTERNAL (Information System Journal), 2024)
Fafiras Kitchen is a family business that focuses on food catering services. This business involves three main operational stages, namely the ordering process, procurement of raw materials, and delivery of products to customers. From the results of observations and interviews, several problems were identified such as the absence of good records in the ordering process resulting in errors in order fulfillment and loss of customer data, dependence on one raw material supplier increases the risk of delays and disruptions in the supply chain and inefficient delivery management caused by human error and no real time tracking, so this has an impact on customer loyalty. This research aims to analyze and model the current business process and provide recommendations for improvement. Modeling is done using Business Process Model and Notation (BPMN) with a qualitative approach to investigate existing business processes. The results of this research can identify areas of improvement to increase the efficiency and effectiveness of MSMEs operations so that MSMEs can better understand, manage, and optimize their business processes. In addition, this research also conducted simulations using the Bizagi Modeler application to test the validity of the business process modeling that has been made. The simulation results show an increase in time in the implementation of business processes.